Photo-crosslinking gelatin hydrogel material as well as preparation method and application thereof
By forming microscopic phase separation structure and interface bonding in gelatin hydrogels, the problem of insufficient mechanical properties in the existing technology is solved by using photocrosslinking technology, high strength and biocompatibility of gelatin hydrogels are achieved, and its application potential in the field of biomedical science has been expanded.
Patent Information
- Application Number
- CN202411759681.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to improve the mechanical properties of gelatin hydrogels while taking into account its biological characteristics and rapid processing advantages.
By forming a microscopic phase separation structure in the gelatin hydrogel and establishing a firm interface bond between the two phases, the photocrosslinking technology is used to achieve rapid cross-linking and high strength of the materials.
It significantly improves the strength and toughness of gelatin hydrogels, overcomes the network defects formed by pure free radical crosslinking, maintains biocompatibility and cell adhesion, and is suitable for 3D printing and biomedical applications.
Smart Images

Figure CN119564930A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical polymer materials, and mainly relates to a photo-crosslinked gelatin hydrogel material and a preparation method and application thereof. Background Art
[0002] The basic concept of tissue engineering is to inoculate living cells onto biocompatible scaffolds and promote cell growth and expansion through culture to eventually form mature tissues. Ideal tissue engineering scaffolds require materials to be biocompatible, promote cell adhesion, and be biodegradable to provide space for tissue regeneration. In addition, in order to match complex biological structures, these materials are also required to have good processability and be compatible with advanced biomanufacturing technologies (such as three-dimensional (3D) bioprinting).
[0003] In this context, gelatin hydrogel, as a natural polymer material, has become a very promising tissue engineering scaffold material due to its excellent biological properties, including biocompatibility, degradability and the ability to support cell adhesion. Among them, methacryloyl-based gelatin (GelMA) hydrogel can achieve rapid photocrosslinking through methacryloyl-based free radical polymerization, and is currently a popular tissue engineering scaffold material. Thanks to the precise spatiotemporal controllability of the photocrosslinking mechanism, GelMA hydrogel can meet the requirements of 3D printing technology, so that complex three-dimensional structures that are difficult to achieve with traditional casting methods can be constructed through 3D printing. These advanced structures show broad application prospects in the fields of artificial organ construction, personalized scaffold preparation and drug screening. However, due to the uncontrollable characteristics of free radical polymerization, the network structure formed by the polymerization has a large number of defects, which makes the mechanical properties of GelMA hydrogel insufficient, limiting its stability, durability and the resolution of the printed structure, thereby limiting its practical application.
[0004] In order to improve the mechanical properties of gelatin hydrogels, researchers have conducted a lot of explorations, and the main strategy is to develop composite materials. Common methods include embedding nanomaterials in the GelMA matrix to form composite hydrogels, or introducing additional networks (such as calcium alginate networks) to construct double network hydrogels. However, these methods usually reduce the gelatin content, thereby weakening the complete biodegradability of pure gelatin and affecting cell adhesion ability, which is not conducive to biological applications. Another strategy is to use the Hofmeister effect to enhance the performance of GelMA hydrogels. This method requires the cross-linked hydrogel to be immersed in a solution containing inorganic salts, organic salts or organic solvents. The ions or solvent molecules in the solution directly interact with the gelatin polymer chains or promote the formation of stronger interactions between polymer chains, thereby enhancing the mechanical strength of the GelMA hydrogel. Although this method retains the degradability and cell adhesion properties of gelatin, it has significant limitations. First, the improvement in the mechanical properties of the hydrogel material obtained by this strategy is reversible, and the hydrogel may return to its original state in an aqueous solution environment. In addition, the salting-out process is harmful to cells and prolongs the preparation time, which limits its practical applicability in 3D printing of complex structures, especially cell-laden structures.
[0005] It can be seen that the existing technology has not yet achieved the goal of improving the mechanical properties of GelMA hydrogel while taking into account its biological properties and rapid processing advantages. Summary of the invention
[0006] The present invention provides a novel photo-crosslinked gelatin hydrogel material and a preparation method and application thereof, which improves the mechanical properties of GelMA hydrogel while taking into account its biological properties and rapid processing advantages.
[0007] The key to improving the mechanical properties of the photocrosslinked gelatin hydrogel of the present invention is that a microscopic phase separation structure is formed inside it, and a strong interface bond is established between the two phases. The effective mechanical conduction between the microphases through the interface improves the strength and toughness of the gelatin hydrogel at the same time, overcoming the performance impact caused by the network defects formed by simple free radical crosslinking. This unique microstructure has been realized and applied in gelatin hydrogel for the first time.
[0008] The photo-crosslinked gelatin hydrogel of the present invention uses gelatin molecules as the only raw material and has the same biocompatibility, degradability, cell adhesion and rapid crosslinking properties as GelMA hydrogel, but its mechanical properties are significantly improved compared to GelMA hydrogel, thereby expanding the application scope of gelatin hydrogel.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] The first object of the present invention is to provide a photo-crosslinked gelatin hydrogel material.
[0011] The photo-crosslinked gelatin hydrogel material is formed by photo-crosslinking three raw materials in a biocompatible medium, and the three raw materials are:
[0012] Photosensitive gelatin derivative modified with o-nitrobenzyl molecules, referred to as component A;
[0013] Double bond functional group modified gelatin derivative, referred to as component B;
[0014] Photoinitiator, referred to as component C.
[0015] The photosensitive gelatin derivative modified with o-nitrobenzyl molecules (i.e. component A) is selected from any structure of components A-1 to A-5:
[0016]
[0017] In the above structural formula, Gelatin represents gelatin, and n≥2, that is, the average number of o-nitrobenzyl molecules (that is, the structures in brackets in the structural formula) on a single gelatin molecular chain is greater than or equal to 2.
[0018] The gelatin is selected from gelatin from pig, cattle and fish;
[0019] The gelatin derivative modified with double bond functional groups, that is, the double bond functional groups in component B are selected from acrylate functional groups, methacrylate functional groups, acrylamide functional groups or methacrylamide functional groups.
[0020] The photoinitiator, referred to as component C, is a substance that can generate free radicals under light;
[0021] Optionally, component C is a water-soluble photoinitiator or a photoinitiator dispersible in water;
[0022] Optionally, component C is LAP (component C-1), I 2959 (component C-2), Eosin-Y (component C-3), benzophenone (component C-4), Na-TPO (component C-5), etc. or a derivative thereof;
[0023] Preferably, component C is LAP, Na-TPO or a derivative thereof;
[0024]
[0025] In some embodiments of the present invention, the mass ratio of component A, component B, and component C is (1-30): (1-30): (0.1-0.9); preferably, the mass ratio of component A, component B, and component C is (2-10): (2-10): (0.1-0.3).
[0026] The second object of the present invention is to provide a method for preparing the photo-crosslinked gelatin hydrogel material.
[0027] The method for preparing the photo-crosslinked gelatin hydrogel material comprises the following steps:
[0028] Component A, component B and component C are dissolved in a biocompatible medium to obtain a hydrogel precursor solution;
[0029] The hydrogel precursor solution undergoes photo-crosslinking under the irradiation of a light source to form a photo-crosslinked gelatin hydrogel material.
[0030] The hydrogel precursor solution can be obtained by any of the following two methods:
[0031] Method 1: dissolving component A in a biocompatible medium to obtain solution A; dissolving component B in a biocompatible medium to obtain solution B; dissolving component C in a biocompatible medium to obtain solution C; and uniformly mixing solution A, solution B and solution C to obtain a hydrogel precursor solution;
[0032] Method 2: Component A, component B and component C are mixed and dissolved in a biocompatible medium to obtain a hydrogel precursor solution.
[0033] In some embodiments of the present invention, the biocompatible medium is selected from distilled water, physiological saline, buffer, decellularized matrix or cell culture medium solution or a combination thereof. Different media can be selected according to different applications.
[0034] In some embodiments of the present invention, the degree of substitution of o-nitrobenzyl molecules in component A (i.e., the molar ratio of o-nitrobenzyl groups to lysine in gelatin molecules) is 1%-40%, preferably 5%-20%; the degree of substitution of double bonds in component B (i.e., the molar ratio of double bonds to lysine in gelatin molecules) is 1%-150%, preferably 30%-100%.
[0035] In some embodiments of the present invention, in the uniformly mixed hydrogel precursor solution, the solid content of component A is 1wt%-30wt%, preferably 2wt%-10wt%; the solid content of component B is 1wt%-30wt%, preferably 2wt%-10wt%; the solid content of component C is 0.1wt%-0.9wt%, preferably 0.1wt%-0.3wt%; the total solid content of component A and component B is 2wt%-60wt%, preferably 5wt%-20wt%.
[0036] In some embodiments of the present invention, the wavelength of the light source is determined according to the absorption wavelength of the o-nitrobenzyl photo-trigger and the photo-initiator, and can be 250-500nm, preferably 300-450nm, and further preferably 365nm, 375nm, 385nm, 395nm, and 405nm.
[0037] The third object of the present invention is to provide an application of the photo-crosslinked gelatin hydrogel material.
[0038] The present invention provides the use of the photo-crosslinked gelatin hydrogel material as a 3D printing (extrusion printing) material-bio-ink;
[0039] The present invention provides the use of the photo-crosslinked gelatin hydrogel material as a 3D printing (DLP) material-bio-ink;
[0040] The present invention provides the use of the photo-crosslinked gelatin hydrogel material as a 3D printing (volume printing) material-bio-ink;
[0041] The invention provides the application of the photo-crosslinked gelatin hydrogel material in preparing microspheres through microfluidics.
[0042] The present invention provides application of the photo-crosslinked gelatin hydrogel material as a carrier for preparing cells, proteins and drugs.
[0043] The present invention provides application of the photo-crosslinked gelatin hydrogel material in preparing wound repair materials and hemostatic materials.
[0044] The photo-crosslinked gelatin hydrogel material of the present invention realizes in-situ polymerization phase separation inside the material and establishes a strong interface between phases by introducing a light-triggered nitroxide free radical and carbon free radical coupling reaction into a traditional photo-initiated free radical polymerization system, thereby realizing the rapid photo-crosslinking preparation of high-strength gelatin hydrogel material. As shown in the following schematic diagram, the technical principle of photo-crosslinking of the photo-crosslinked gelatin hydrogel of the present invention is as follows: the double bond functional group in component B and component C-photoinitiator rapidly undergo free radical polymerization under light to form a hard phase with a high crosslinking density; subsequently, the o-nitrobenzyl group in component A reacts with the free radical generated by component C-photoinitiator under light conditions to generate nitroxide free radicals, which rapidly crosslink the carbon free radical growth chain on the surface of the hard phase and finally form a hydrogel. This crosslinking mechanism promotes the formation of a phase separation structure in the gelatin matrix and establishes a strong interface bond between the two phases, thereby significantly enhancing the mechanical properties of the gelatin hydrogel.
[0045]
[0046] Schematic diagram of phase separation structure formation
[0047] Through the above technical solution conceived by the present invention, compared with the prior art, the present invention has the following advantages:
[0048] (1) The gelatin hydrogel provided by the present invention has excellent mechanical properties, and its mechanical properties are significantly improved compared with the currently widely used GelMA hydrogel.
[0049] (2) The gelatin hydrogel of the present invention uses only gelatin molecules as raw materials and does not need to be compounded with other materials. It fully retains the inherent advantages of gelatin molecules, has excellent biocompatibility and cell adhesion, and can be completely degraded.
[0050] (3) The gelatin hydrogel of the present invention has a fast crosslinking speed, which is comparable to that of GelMA hydrogel, and can reach the crosslinking point within 5 seconds and achieve complete crosslinking within 10 seconds.
[0051] (4) The gelatin hydrogel of the present invention has excellent processing properties, and complex three-dimensional structures can be prepared by 3D printing technology (such as extrusion printing, DLP printing and volume printing), and hydrogel microspheres of different sizes can also be prepared by microfluidic technology.
[0052] The gelatin hydrogel provided by the present invention can be used to prepare cell scaffolds with excellent performance, support higher-precision 3D printing structures with cells, and is expected to further expand the application potential of gelatin hydrogel in the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is the characterization of the microscopic phase structure of the photo-cross-linked gelatin hydrogel by atomic force microscopy in Example 8.
[0054] Figure 2 This is the characterization of the microscopic phase structure of the photo-cross-linked gelatin hydrogel by scanning transmission electron microscopy in Example 9.
[0055] Figure 3 In Example 10, the microscopic phase separation structure of the photo-cross-linked gelatin hydrogel was characterized by fluorescent labeling technology.
[0056] Figure 4 The real-time rheological diagram of the photogelation of the hydrogel precursor solutions of Formula 1 and Comparative Formula 1 in Example 12.
[0057] Figure 5 These are the tensile stress-strain curves of the hydrogel materials corresponding to Formulation 7, Formulation 13, Comparative Formulation 3 and Comparative Formulation 5 in Example 13.
[0058] Figure 6 The degradation rate curves of the hydrogel samples corresponding to the different formulations listed in Table 5 in Example 14.
[0059] Figure 7The cytotoxicity and cell proliferation of Formulation 7 and Comparative Formulation 3 measured by the CCK-8 method in Example 15.
[0060] Figure 8 The cell adhesion of Formula 1, Formula 7, Comparative Formula 1 and Comparative Formula 3 was demonstrated by fluorescently labeling the cytoskeleton in Example 16.
[0061] Fig. 9 This is a visual diagram of the effect of using the hydrogel of Formula 13 as the bio-ink combined with the extrusion printing technology in Example 17.
[0062] Fig.10 This is a visual diagram of the effect of using Formula 1, Formula 7, Comparative Formula 1 and Comparative Formula 3 hydrogels as bio-inks combined with DLP printing technology in Example 18.
[0063] Fig.11 This is a visual representation of the effect of using the hydrogel of Formula 7 as the bio-ink combined with the volumetric printing technology in Example 19.
[0064] Fig.12 This is a visual representation of the effect of preparing microspheres by microfluidics using the precursor hydrogel solution of Formula 1 in Example 20.
[0065] Fig.13 Example 21 shows ear cartilage tissue constructed by combining Formula 7 hydrogel as DLP printing bio-ink with stem cell culture technology.
[0066] Fig.14 This is a diagram showing the effect of using the hydrogel of Formula 13 as a liver hemostatic material in Example 23. DETAILED DESCRIPTION
[0067] In order to facilitate the understanding of the present invention, the present invention is described more comprehensively below in conjunction with the accompanying drawings and specific embodiments, and preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0068] Example 1: Synthesis of Component A-1
[0069]
[0070] (1) Synthesis of compound 1: The synthesis was carried out according to the method disclosed in reference Yunlong Yang; Jieyuan Zhang; Zhenzhen Liu; Qiuning Lin; Xiaolin Liu; Chunyan Bao; Yang Wang; Linyong Zhu. Adv. Mater. 2016, 28, 2724. 1H NMR (400MHz, DMSO-d6) δ7.57(s,1H),7.16(s,1H),5.14(t,J=5.9Hz,1H),4.80(d,J=12.9Hz,1H),4.5 9(d,J=12.9Hz,1H), 4.11(t,J=6.2Hz,2H), 3.85(s,3H), 2.52(t,J=9.2Hz,2H), 2.08(t,J=9.4Hz,2H).
[0071] (2) Synthesis of Compound 2: Compound 1 (20 g, 70 mmol) was dissolved in anhydrous N,N-dimethylformamide (100 mL), and then anhydrous dichloromethane (200 mL) was added, followed by (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride) (26.9 g, 140 mmol) and N-hydroxysuccinimide (16.2 g, 140 mmol), and the mixture was reacted overnight at room temperature. After the reaction was completed, the solvent was dried and wet column chromatography (first using dichloromethane to remove impurities, and then using 2% methanol / dichloromethane to separate the product) was performed, with a yield of more than 90%. 1 H NMR (400MHz, DMSO-d6) δ7.57(s,1H),7.16(s,1H),5.14(t,J=5.9Hz,1H),4.80(d,J=12.9Hz,1H),4.59(d,J= 12.9Hz, 1H), 4.09 (t, J = 6.4Hz, 2H), 3.85 (s, 3H), 2.79 (s, 2H), 2.57 (t, J = 9.2Hz, 2H), 2.09 (t, J = 9.3Hz, 2H).
[0072] (3) Synthesis of component A-1: Gelatin (1 g, specifically in this embodiment, type A gelatin from pig skin with a concentration of 300 Bloom / g) was dissolved in 50°C Dulbecco's phosphate buffer (10 wt%). Compound 2 (0.1 g) was dissolved in dimethyl sulfoxide (1 mL). The dimethyl sulfoxide solution of compound 2 was added to the gelatin mixture. The mixture was then stirred at 40°C for 30 minutes. Unreacted reagents were removed by dialysis. The product was freeze-dried and stored at -20°C for subsequent use. The degree of substitution of the o-nitrobenzyl group was determined by UV-visible spectrophotometry.
[0073] Example 2: Synthesis of Component A-2
[0074]
[0075] (1) Synthesis of compound 3: The synthesis was carried out according to the method disclosed in reference Yunlong Yang; Jieyuan Zhang; Zhenzhen Liu; Qiuning Lin; Xiaolin Liu; Chunyan Bao; Yang Wang; Linyong Zhu. Adv. Mater. 2016, 28, 2724. 1 H NMR(400MHz,DMSO-d6)δ8.00(d,J=8.7Hz,1H),7.02–6.93(m,2H),5.18(t,J=5.9Hz,1H),4 .75(d,J=5.9Hz,2H), 4.06(d,J=12.3Hz,2H), 2.54(t,J=9.2Hz,2H), 2.07(t,J=9.3Hz,2H).
[0076] (2) Synthesis of Compound 4: Refer to the synthesis method of Compound 2. 1 The structure was determined by H NMR spectroscopy. 1 H NMR(400MHz, DMSO-d6)δ8.00(d,J=8.7Hz,1H),7.02–6.93(m,2H),5.18(t,J=5.9Hz,1H),4.75(d, J=5.9Hz, 2H), 4.06 (d, J=12.6Hz, 2H), 2.79 (s, 2H), 2.57 (t, J=9.2Hz, 2H), 2.07 (t, J=9.1Hz, 2H).
[0077] (3) Synthesis of component A-2: refer to the synthesis method of component A-1 (using type A gelatin from tilapia skin with 280 Bloom / g). Determine the degree of substitution of o-nitrobenzyl by UV-visible spectrophotometry.
[0078] Example 3: Synthesis of Component A-3
[0079]
[0080] (1) Synthesis of compound 5: The synthesis was carried out according to the method disclosed in reference Yunlong Yang; Jieyuan Zhang; Zhenzhen Liu; Qiuning Lin; Xiaolin Liu; Chunyan Bao; Yang Wang; Linyong Zhu. Adv. Mater. 2016, 28, 2724. 1H NMR (400MHz, DMSO-d6) δ7.48 (s, 1H), 7.10 (s, 1H), 4.11 (t, J = 6.2Hz, 2H), 3.85 (s, 3H), 2. 83(d,J=7.5Hz,2H), 2.52(t,J=9.2Hz,2H), 2.08(t,J=9.4Hz,2H), 1.20(t,J=7.5Hz,3H).
[0081] (2) Synthesis of Compound 6: Refer to the synthesis method of Compound 2. 1 The structure was determined by H NMR spectroscopy. 1 H NMR (400MHz, DMSO-d6) δ7.48 (s, 1H), 7.07 (s, 1H), 4.09 (t, J = 6.4Hz, 2H), 3.85 (s, 3H), 2.83 (d, J=7.5Hz,2H),2.79(s,2H),2.57(t,J=9.2Hz,2H),2.09(t,J=9.3Hz,2H),1.20(t,J=7.5Hz,3H).
[0082] (3) Synthesis of component A-3: refer to the synthesis method of component A-1 (select 300 Bloom / g of type B gelatin from cowhide). Determine the degree of substitution of o-nitrobenzyl by UV-visible spectrophotometry.
[0083] Example 4: Synthesis of Component A-5
[0084]
[0085]
[0086] (1) Synthesis of compound 7: The synthesis was carried out according to the method disclosed in reference Yunlong Yang; Jieyuan Zhang; Zhenzhen Liu; Qiuning Lin; Xiaolin Liu; Chunyan Bao; Yang Wang; Linyong Zhu. Adv. Mater. 2016, 28, 2724. 1 H NMR (400MHz, DMSO-d6) δ7.55(s,1H),7.16(s,1H),5.14(t,J=5.9Hz,1H),4.80(d,J=12.9H z, 1H), 4.59 (d, J = 12.9Hz, 1H), 4.28 (t, J = 6.3Hz, 2H), 3.85 (s, 3H), 2.71 (t, J = 6.3Hz, 2H).
[0087] (2) Synthesis of Compound 8: Refer to the synthesis method of Compound 2. 1 The structure was determined by H NMR spectroscopy. 1 H NMR (400MHz, DMSO-d6) δ7.55(s,1H),7.16(s,1H),5.14(t,J=5.9Hz,1H),4.80(d,J=12.9Hz,1H) ,4.59(d,J=12.9Hz,1H),4.32(t,J=6.3Hz,2H),3.85(s,3H),2.84(t,J=6.3Hz,2H),2.79(s,2H).
[0088] (3) Synthesis of component A-5: refer to the synthesis method of component A-1 (select 300 Bloom / g of type A gelatin from pig skin). Determine the degree of substitution of o-nitrobenzyl by UV-visible spectrophotometry.
[0089] Example 5: Synthesis of Component B-1
[0090] Gelatin (1 g, specifically in this example, 300 Bloom / g of porcine skin-derived type A gelatin) was dissolved in 50°C Dulbecco's phosphate buffer (10 wt%). Methacrylic anhydride (0.4 mL) was gradually added to the gelatin mixture and stirred for 3 hours. After each addition of methacrylic anhydride, the pH was adjusted to 7.4 with sodium hydroxide (5 M). Dialyze with deionized water for 2 days. The product was freeze-dried and stored at -20°C until further use. 1 H-NMR determined that the degree of substitution of methacryloyl groups (mainly methacrylamide groups) on gelatin molecules was 40%.
[0091] Example 6: Synthesis of Component B-2
[0092] Dissolve 3-hydroxypropyl methacrylate (10g, 70mmol) in anhydrous dichloromethane (100mL), add p-nitrophenyl chloroformate (28g, 140mmol) and triethylamine (14.1g, 140mmol), and react at room temperature for 5 hours. After the reaction is completed, the solvent is dried and wet column chromatography (first use petroleum ether / dichloromethane to remove impurities, and then use dichloromethane to separate the product) is performed to obtain a purified active intermediate. Gelatin (1g, specifically in this embodiment, 300Bloom / g type A gelatin from pig skin is selected) is dissolved in 50°C Dulbecco's phosphate buffer (10wt%). The active intermediate (0.8g) is gradually added to the gelatin mixture and stirred for 3 hours. After each addition of the active intermediate, the pH value is adjusted to 7.4 with sodium hydroxide (5M). Dialyze with deionized water for 2 days. The product is freeze-dried and stored at -20°C until further use. By 1H-NMR determined that the degree of substitution of methacrylate groups on the gelatin molecules was 40%.
[0093] Example 7: Preparation of photo-crosslinked gelatin hydrogel
[0094] Preparation of the gelatin hydrogel of the present invention: Component A, component B and component C-1 are heated and dissolved in Dulbecco's phosphate buffer, and the gel solution is heated at 395 nm, 20 mW / cm 2 Under the conditions, light is irradiated for a certain period of time to obtain different photo-crosslinked gelatin hydrogels. The preparation method is detailed in Table 1. Component C-1 is the LAP described in the invention content of the specification.
[0095] Preparation of control hydrogel (GelMA hydrogel): Component B and component C-1 were dissolved in Dulbecco's phosphate buffer by heating, and the gel solution was heated at 395 nm, 20 mW / cm 2 Under the conditions of light for a certain period of time, gelatin hydrogels with different comparative formulas were obtained. The preparation methods are detailed in Table 2.
[0096] Tables 1 and 2 show the gel solid content and component compositions of preferred representative photo-crosslinked gelatin hydrogels and comparative example hydrogels.
[0097] Table 1
[0098]
[0099]
[0100] Table 2
[0101]
[0102] Example 8: Structural characterization of photocrosslinked gelatin hydrogel under atomic force microscopy
[0103] In this embodiment, an atomic force microscope was used to measure the microstructure of photo-crosslinked gelatin hydrogel and GelMA hydrogel. Using a Dimension Icon atomic force microscope, the hydrogel samples of formula 13, formula 14 and comparative formula 5 were measured in Tapping mode, and the quantitative nanomechanics of different samples were analyzed. Before the experiment, the gel samples were pre-soaked in saline to reach equilibrium and fixed to a glass plate with glue. A non-conductive silicon nitride microcantilever was used as a probe, and the test was carried out under the conditions of a resonant frequency of 65kHz and a spring constant of 0.350N / m. Figure 1 As shown, the phase separation microstructure with modulus difference can be clearly observed in the photo-crosslinked gelatin hydrogel (Formula 13 and Formula 14). This result further verifies the phase separation characteristics of the hydrogel. In the hydrogel sample of comparative formula 5, the existence of phase separation structure is almost not observed.
[0104] Example 9: Structural characterization of photocrosslinked gelatin hydrogel under scanning transmission electron microscopy
[0105] In this example, scanning transmission electron microscopy was used to measure the microstructure of photo-cross-linked gelatin hydrogel and GelMA hydrogel. The hydrogel samples of Formula 13, Formula 14 and Comparative Formula 5 were soaked in water to remove unreacted photoinitiator, and then vacuum dried at 25°C. The dried samples were cut with a Leica EMUC7 / FC7 cryo-ultramicrotome at -70°C to obtain frozen sections. Frozen sections with a thickness of 100 nm were collected on a porous carbon film supported by a 230-mesh copper transmission electron microscope grid. Subsequently, a FEI Talos F200X scanning transmission electron microscope was used to observe the bright field and high-angle annular dark field at a voltage of 250 kV. Figure 2 As shown in the figure, it can be clearly observed that the photo-crosslinked gelatin hydrogels (Formula 13 and Formula 14) have obvious phase separation microstructures in the bright field of the scanning transmission electron microscope. This result further verifies the phase separation characteristics of the photo-crosslinked gelatin hydrogel. In the hydrogel sample of the comparative formula 5, the existence of phase separation structure is almost not observed.
[0106] Example 10: Characterization of the microscopic phase separation structure of photo-crosslinked gelatin hydrogel by fluorescence labeling technology
[0107] In this example, rhodamine B was used to chemically modify component B-1 to track the microscopic phase separation structure and distribution of component B-1 in the photo-crosslinked gelatin hydrogel.
[0108] Preparation of rhodamine B modified component B-1: Component B-1 (1 g) was dissolved in Dulbecco's phosphate buffer (10 wt%) at 40°C. Subsequently, rhodamine B 5-isothiocyanate (0.1 g) was dissolved in dimethyl sulfoxide (1 mL) to prepare a solution, which was added to the mixed solution of component B-1. After stirring at 40°C for 30 minutes, the unreacted reagent was removed by dialysis. The final product was lyophilized and stored at -20°C for subsequent use.
[0109] Preparation of Rhodamine B modified hydrogel samples: Component B-1 in Formula 7, Formula 8 and Comparative Formula 3 was replaced with component B-1 modified with Rhodamine B to prepare Rhodamine modified hydrogel samples of Formula 7, Formula 8 and Comparative Formula 3, respectively.
[0110] Microstructure characterization of hydrogel samples: The hydrogel samples with different formulations were measured by confocal microscopy. The results showed that granular structures with a diameter of about 800-1000nm were observed in the hydrogels of the experimental group ( Figure 3). In contrast, the hydrogel of comparative formula 3 did not show obvious phase separation structure after cross-linking under the same conditions.
[0111] Example 11: Testing the gelation time of photo-crosslinked gelatin hydrogel by rheometer
[0112] The test was carried out using a HAAKE MARS rheometer on a test platform (20 mm in diameter) at 37° C. The gel point of the hydrogel (the moment when G’ exceeds G”) was determined by real-time monitoring of the storage modulus (G’) and loss modulus (G”).
[0113] The experimental results show (Table 3) that the photo-crosslinked gelatin hydrogel and the control GelMA hydrogel have similar gelation times. At a low solid content of 5wt%, both can quickly gel and reach a stable state within 5 seconds after illumination. When the solid content increases to 10wt% and 20wt%, the gelation time is 2-3s, indicating that both materials have the characteristics of rapid gelation after photo-crosslinking.
[0114] Table 3
[0115]
[0116]
[0117] Example 12: Testing the Mechanical Properties of Photocrosslinked Gelatin Hydrogels by Rheometer
[0118] In view of the weak tensile strength and large error of the hydrogel at 5wt% solid content, the mechanical properties of photo-crosslinked gelatin hydrogel and GelMA hydrogel at 5wt% solid content were evaluated by rheological testing in this example. The test was carried out on a test platform (20mm in diameter) at 37°C using a HAAKE MARS rheometer. The storage modulus (G') and loss modulus (G") were monitored in real time.
[0119] The experimental results show that the mechanical properties of hydrogels with different formulations under UV conditions are significantly different. Taking formulation 1 and comparative formulation 1 as examples, the real-time rheological curves show ( Figure 4 ), the storage modulus of the hydrogel of Formula 1 is 632Pa, while the storage modulus of Formula 1 is increased to 2024Pa.
[0120] Further studies have shown that photo-crosslinked gelatin hydrogels with other ratios also exhibit a storage modulus significantly higher than that of comparative formula 1. The specific data are shown in Table 4.
[0121] Table 4
[0122] Hydrogel formulation Gel strength (Pa) Recipe 1 2024 Recipe 2 1635 Recipe 3 1861 Recipe 4 1983 Recipe 5 1579 Recipe 6 1774 Comparison formula 1 632 Comparison formula 2 474
[0123] Example 13: Evaluation of the mechanical properties of photocrosslinked gelatin hydrogels by tensile testing
[0124] For formulations with a solid content higher than 5 wt%, this example compares the mechanical properties of photocrosslinked gelatin hydrogel and GelMA hydrogel by tensile testing. The stress-strain curve was obtained by tensile testing, and the maximum tensile strength and toughness (work of fracture) were calculated based on the curve. Among them, toughness (unit: kJ / m 3 ) is calculated by integrating the area under the stress-strain curve.
[0125] The tensile performance test was completed using a GT-TCS-2000 tensile testing machine. The test sample was a dumbbell-shaped specimen with a length of 3 mm, a width of 1 mm, and a thickness of 1 mm. The test speed was 30 mm / min. The test results showed that at a solid content of 10 wt%, the tensile strength and toughness of the hydrogel of the comparative formula 3 were 182 kPa 252 kJ / m 3 The tensile strength and toughness of the hydrogel of formula 7 were increased to 590 kPa and 1302 kJ / m 3 ( Figure 5 ). When the solid content was further increased to 20 wt%, the tensile strength and toughness of the hydrogel of Formula 13 reached 1013 kPa and 1132 kJ / m respectively. 3 In comparison, the tensile strength and toughness of the comparative formula 5 are only 402kPa and 307kJ / m 3 ( Figure 5 ). These results indicate that the tensile strength of photocrosslinked gelatin hydrogels is significantly better than that of GelMA hydrogels at both low and high solid content conditions.
[0126] In addition, at the same solid content, the tensile strength and toughness of other photo-crosslinked gelatin hydrogels with different ratios are also significantly higher than those of GelMA hydrogels, and the specific data are shown in Table 5. These results further verify the significant advantages of the photo-crosslinked gelatin hydrogels of the present invention in terms of mechanical properties.
[0127] Table 5
[0128] Hydrogel formulation Tensile strength(kPa) <![CDATA[Toughness (kJ / m 3 )]]> Recipe 7 590 1302 Recipe 8 495 1257 Recipe 9 530 1315 Recipe 10 571 1206 Recipe 11 533 976 Recipe 12 497 991 Recipe 13 1013 1132 Recipe 14 1207 1230 Recipe 15 1143 1189 Recipe 16 1097 1156 Recipe 17 983 1075 Recipe 18 892 851 Comparison formula 3 182 252 Comparison formula 4 149 180 Comparison formula 5 402 307 Comparison formula 6 304 157
[0129] Example 14: Degradation properties of photo-crosslinked gelatin hydrogel materials
[0130] This example evaluates the degradation performance of photo-crosslinked gelatin hydrogel and GelMA hydrogel by in vitro degradation test. In the experiment, the hydrogels of Formula 1, Formula 7, Formula 13, Comparative Formula 1, Comparative Formula 3 and Comparative Formula 5 were prepared into discs with a diameter of 10 mm and a thickness of 3 mm by a mold. Subsequently, these hydrogel samples were immersed in collagenase I solution (1 U / mL), and the relative changes in the sample mass were measured regularly to study their degradation behavior.
[0131] The results showed that under the same solid content conditions, the degradation rate of photocrosslinked gelatin hydrogel was basically the same as that of GelMA hydrogel (Table 6 and Figure 6 ). This indicates that the photo-crosslinked gelatin hydrogel has improved mechanical properties while maintaining similar degradability to that of GelMA hydrogel, indicating that the mechanical enhancement strategy of the present invention for gelatin hydrogel is superior to the previous composite doping strategy.
[0132] Table 6
[0133] Hydrogel formulation Gel solid content (wt%) Complete degradation time (h) Recipe 1 5 4 Recipe 2 5 4 Recipe 3 5 4 Recipe 4 5 4 Recipe 5 5 4 Recipe 6 5 4 Recipe 7 10 16 Recipe 8 10 16 Recipe 9 10 16 Recipe 10 10 16 Recipe 11 10 16 Recipe 12 10 16 Recipe 13 20 36 Recipe 14 20 36 Recipe 15 20 36 Recipe 16 20 36 Recipe 17 20 36 Recipe 18 20 36 Comparison formula 1 5 4 Comparison formula 2 5 4 Comparison formula 3 10 16 Comparison formula 4 10 16 Comparison formula 5 20 36 Comparison formula 6 20 36
[0134] Example 15: Cytotoxicity test of photo-crosslinked gelatin hydrogel material
[0135] According to ISO 10993-5 standard, this example uses the leachate in the hydrogel to detect the cytotoxicity of the hydrogel of Formula 7 and Comparative Formula 3 on the fibroblast (L929) line by CCK-8 method. The experimental results show that at different leachate concentrations, the cytotoxicity of Formula 7 and Comparative Formula 3 is very low, and the cell survival rate is always over 90% ( Figure 7 A), indicating that both hydrogels have good safety in terms of biocompatibility.
[0136] In addition, this example further encapsulated L929 cells in the hydrogel and cultured them in a 37°C incubator for 3 days and 10 days, respectively. At different time points, the CCK-8 method was used to evaluate the cell proliferation activity encapsulated in the hydrogels of Formula 7 and Comparative Formula 3. During the entire culture period (3 to 10 days), both hydrogels showed significant cell proliferation ( Figure 7 B). Among them, the hydrogel of formula 7 showed an effect comparable to that of comparative formula 3 in supporting cell proliferation, further demonstrating its excellent performance in biocompatibility and ability to support cell growth.
[0137] Example 16: Cell Adhesion Test of Photocrosslinked Gelatin Hydrogel Material
[0138] The adhesion ability of hydrogel to cells is a key prerequisite for cell diffusion, migration and multiple functions. In this example, L929 cells were cultured on the hydrogel surfaces of Formula 7 and Comparative Formula 3 to evaluate the cell adhesion performance of photo-crosslinked gelatin hydrogel and GelMA hydrogel.
[0139] The experimental results showed that after 16 hours of culture, the cells on the hydrogel surfaces of Formula 7 and Comparative Formula 3 formed observable pseudopodia, which further extended after 8 hours ( Figure 8 A). By quantitatively analyzing the number of cells and cell aspect ratio on the hydrogel surface, it was found that the number and speed of cell adhesion of the hydrogels of Formula 7 and Comparative Formula 3 were similar. In addition, the hydrogels of Formula 1 and Comparative Formula 1 also showed the same trend in cell adhesion ( Figure 8 B).
[0140] The above results show that the cell adhesion performance of photo-crosslinked gelatin hydrogel is comparable to that of GelMA hydrogel, and both exhibit excellent cell adhesion. This shows that the mechanical enhancement strategy of the present invention for gelatin hydrogel maintains its biological properties while improving the mechanical properties, which is superior to the previous composite doping strategy and lays a foundation for its further development in applications related to cell diffusion and migration.
[0141] Example 17: Application of photo-crosslinked gelatin hydrogel material in 3D printing (extrusion printing)
[0142] Photo-crosslinked gelatin hydrogel can be used as bio-ink to construct a three-dimensional structure through extrusion printing technology. In this example, the bio-extrusion printer BioMaker 4 was used to prepare the three-dimensional printed hydrogel structure of formula 13. The key parameters during the printing process are as follows: the ink cartridge temperature is set to 42°C, the printing platform temperature is set to 25°C, the layer height is set to 0.2mm, the layer width is set to 1.2mm, the printing speed is 3mm / s, and the extrusion speed is 0.3mm 3 During the printing process, each layer of material is exposed to 395nm ultraviolet light (0.5W / cm 2 ) was irradiated for 10 seconds to complete the photo-crosslinking gelation. After printing, the photo-crosslinked gelatin hydrogel of formula 13 successfully formed a stable and precise three-dimensional structure ( Fig. 9 ), verifying its excellent adaptability and molding ability as a bio-ink.
[0143] Example 18: Application of photo-crosslinked gelatin hydrogel material in 3D printing (DLP)
[0144] The photo-crosslinked gelatin hydrogel material proposed in the present invention is very suitable for digital light processing (DLP) printing due to its fast photocuring speed and excellent mechanical properties. This example takes the hydrogels of Formula 1, Formula 7 and Comparative Formula 1 and Comparative Formula 3 as examples to explore their application in DLP printing.
[0145] In the experiment, 0.03wt% of lemon yellow (photoresist) was added to the precursor gel solution of Formula 1, Formula 7 and Comparative Formula 1 and Comparative Formula 3 to prepare DLP printing ink. After the printing ink was loaded into the liquid tank, the printing process was optimized by adjusting the light source intensity and exposure time, and finally a fine three-dimensional structure hydrogel ( Fig.10 The results show that under the same printing conditions, the hydrogels of Formula 1 and Formula 7 exhibit good printing fidelity and formability due to their excellent mechanical properties, and can maintain the integrity of complex three-dimensional structures. However, the hydrogels of Comparative Formula 1 and Comparative Formula 3 cannot effectively support fine structures due to their insufficient mechanical properties, resulting in printing failure or structural deformation.
[0146] This experiment further verified the significant advantages of photo-crosslinked gelatin hydrogel in DLP printing. Its excellent mechanical properties and printing accuracy enable it to better achieve fine three-dimensional structure manufacturing compared to GelMA hydrogel, providing an innovative material choice for tissue engineering and biomedical applications.
[0147] Example 19: Application of photo-cross-linked gelatin hydrogel material in 3D printing (volume printing).
[0148] Traditional 3D bioprinting technology usually takes a long time to manufacture large-scale tissue structures. Volumetric printing technology can quickly construct large, free-form three-dimensional structures, which not only significantly shortens printing time, but also can produce prints with high cell density. The photo-cross-linked gelatin hydrogel material of the present invention is well suited for this processing method due to its excellent photocuring properties. In this example, the hydrogel of Formula 7 is taken as an example. The precursor gel solution is transferred to a glass bottle container, and volumetric printing is performed using a commercial volumetric three-dimensional printer Tomolite V1. By adjusting the exposure parameters to adapt to the characteristics of different structures and optimizing the printing process, a hydrogel with a fine three-dimensional structure was successfully prepared ( Fig.11 ).
[0149] The experimental results show that the application of the photo-cross-linked gelatin hydrogel of the present invention in volumetric printing not only exhibits excellent processing adaptability, but also can achieve rapid manufacturing of complex three-dimensional structures.
[0150] Example 20: Application of photo-crosslinked gelatin hydrogel material in preparation of microspheres using microfluidic technology
[0151] The photo-cross-linked gelatin hydrogel of the present invention can be processed into microspheres of different sizes, which are suitable for various biomedical fields such as cell delivery and drug delivery. This embodiment uses the high-throughput hydrogel microsphere preparation system YXTP02-01 to prepare hydrogel microspheres. In the experiment, the aqueous phase (the precursor hydrogel solution of Formula 1) and the organic phase (mineral oil containing 1wt% surfactant) were pumped into the microfluidic chip by a syringe pump. By adjusting the pumping speed of the aqueous phase and the oil phase, the size of the microspheres can be precisely controlled. Subsequently, a 395nm ultraviolet lamp is used to quickly photo-cross-link and cure the generated microspheres. Fig.12 As shown in the figure, thanks to the rapid light curing and mechanical enhancement of photo-crosslinked gelatin hydrogel, this processing method can efficiently prepare microsphere particles with uniform particle size and complete morphology. This result shows the significant advantages of photo-crosslinked gelatin hydrogel in the preparation of microspheres, and provides the possibility for its wide application in the fields of cell carriers, drug release systems, etc.
[0152] Example 21: Application of photo-cross-linked gelatin hydrogel in the preparation of cell, protein and drug carriers.
[0153] With its excellent mechanical properties and high compatibility with high-resolution DLP printing technology, photo-crosslinked gelatin hydrogels are expected to be used to manufacture tissue substitutes or organoids with fine structures with the support of in vitro cell culture technology. Fig.13 A, 13B). In this example, the hydrogel of formula 7 was mixed with mouse bone marrow mesenchymal stem cells (mBMSCs), and a three-dimensional structure of ear cartilage encapsulating mBMSCs was constructed by DLP printing technology. The cells were cultured in chondrogenic induction medium for 7 days, 14 days and 21 days to evaluate the survival and differentiation of the cells. The experimental results showed that the content of intracellular acidic mucopolysaccharide increased significantly with the extension of culture time ( Fig.13 C), and the expression of type II collagen also gradually increased ( Fig.13 D) These results indicate that the combination of DLP printing technology and stem cell culture technology can effectively achieve the in vitro construction of ear cartilage tissue.
[0154] This example demonstrates the significant application potential of photo-crosslinked gelatin hydrogels in the field of fine bioprocessing, especially in the construction of high-precision tissue substitutes and organoids, providing new possibilities for tissue engineering and regenerative medicine.
[0155] Example 22: Application of photo-crosslinked gelatin hydrogel material in wound repair
[0156] The skin defect wounds on the back of SD rats were selected and divided into two groups for skin wound repair experiments: Formula 7 hydrogel (group a) and suture group (group b). A circular skin defect with a diameter of 1 cm was constructed on the back of SD rats. For group a, the formula 7 hydrogel precursor solution was injected into the skin defect, and the solution was waited for full filling and penetration. Then, under the irradiation of a 395nm LED light source, the hydrogel was in situ cured at the skin defect to achieve the closure of the wound. Group b was a blank control group, and no treatment was done on the damaged skin. The wounds of each group were observed, and the repair effects within 7 days were recorded. The experimental results showed that compared with group b, group a had a faster repair rate. On the seventh day, the remaining wound area of group a was much smaller than that of group b, and there was no obvious scar tissue formation. It can be seen that the above-mentioned photo-cross-linked gelatin hydrogel can be used for skin wound repair.
[0157] Example 23: Application of photo-crosslinked gelatin hydrogel material in liver hemostasis:
[0158] SD rats were used to evaluate the hemostatic effect of photo-cross-linked gelatin hydrogel. The liver hemostasis experiment was conducted in two groups: Formula 7 hydrogel (Group a) and blank control (Group b). SD rats were anesthetized by intraperitoneal injection of chloral hydrate (4% aqueous solution) with an injection dose of 0.9 mL / 100 g. After deep anesthesia, the rats were shaved with a shaver on the front chest and disinfected with iodine. Then an incision of about 4 cm long was made along the midline of the abdominal cavity to open the abdominal cavity and expose the liver. An incision of about 2 cm was made in the left lobe of the liver. In Group a, Formula 13 hydrogel precursor solution was added to the incision to cover the cut surface, and 395 nm LED light was used for 1 min to form gel to stop bleeding; Group b did not do any treatment, allowing the bleeding from the liver incision to coagulate naturally, and the bleeding was absorbed with gauze. The amount of bleeding and the bleeding time ( Fig.14 ). After the experiment, the hydrogel in group a was cross-linked in situ at the incision and the cut wound was isolated. The liver was put back into the abdominal cavity and sutured. Group b was sutured directly without treatment. After 14 days, the recovery of the liver of SD rats was observed. The rats were killed by intraperitoneal injection of an overdose of the anesthetic chloral hydrate (4% aqueous solution, 2.7ml / 100g). The abdominal cavity was opened along the midline of the thorax to observe the recovery of the liver of the three groups of rats, and photographed and recorded. At the same time, the tissue of the injured liver was sampled, and the specimens were fixed with 4% formalin solution for 2d. After dehydration, they were embedded in paraffin and sliced with a slicer. The thickness of the sample was 5μm. Finally, the specimens were stained with H&E and photographed and observed with an optical microscope. The experimental results showed that the liver of group a recovered well, the hydrogel was completely degraded, no adhesion occurred, and new liver tissue grew out of the liver incision. Adhesion of the liver to the omentum was common in group b. H&E staining showed that the surface of the liver in the experimental group was smooth and round, with abundant blood vessels and a clear liver interface. H&E staining of the liver with adhesion revealed that the liver interface was uneven, the liver was adhered to the omentum tissue, and there were deposited inflammatory cells at the interface.
[0159] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A photo-crosslinked gelatin hydrogel material, characterized in that: It is made of three raw materials that are cross-linked by light in a biocompatible medium. The three raw materials are: Component A: photosensitive gelatin derivative modified with o-nitrobenzyl molecules; Component B: gelatin derivative modified with double bond functional groups; Component C: Photoinitiator.
2. A photo-crosslinked gelatin hydrogel material according to claim 1, characterized in that: The photosensitive gelatin derivative modified with o-nitrobenzyl molecules is selected from any structure of components A-1 to A-5: In components A-1 to A-5, Gelatin represents gelatin, and n≥2, that is, the average number of o-nitrobenzyl molecules on a single gelatin molecule chain is greater than or equal to 2; The gelatin is selected from gelatin from pig, cattle and fish sources.
3. A photo-crosslinked gelatin hydrogel material according to claim 1, characterized in that: The double bond functional group in the double bond functional group modified gelatin derivative is selected from acrylate functional group, methacrylate functional group, acrylamide functional group or methacrylamide functional group; The gelatin is selected from gelatin from pig, cattle and fish sources.
4. A photo-crosslinked gelatin hydrogel material according to claim 1, characterized in that: The photoinitiator is a water-soluble photoinitiator or a photoinitiator dispersible in water; The photoinitiator is selected from component C-1, component C-2, component C-3, component C-4, component C-5 or derivatives of these components; 5. The photo-crosslinked gelatin hydrogel material according to claim 1, characterized in that: The mass ratio of component A, component B and component C is (1-30): (1-30): (0.1-0.9); preferably, the mass ratio of component A, component B and component C is (2-10): (2-10): (0.1-0.3).
6. The method for preparing a photo-crosslinked gelatin hydrogel material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Component A, component B and component C are dissolved in a biocompatible medium to obtain a hydrogel precursor solution; The hydrogel precursor solution undergoes photo-crosslinking under the irradiation of a light source to form a photo-crosslinked gelatin hydrogel material.
7. The method for preparing a photo-crosslinked gelatin hydrogel material according to claim 6, characterized in that: The biocompatible medium is selected from distilled water, physiological saline, buffer, decellularized matrix or cell culture medium solution, or a combination of these.
8. The method for preparing a photo-crosslinked gelatin hydrogel material according to claim 6, characterized in that: In component A, the molar ratio of o-nitrobenzyl groups to lysine in gelatin molecules is 1%-40%, preferably 5%-20%; In component B, the molar ratio of double bonds to lysine in gelatin molecules is 1%-150%, preferably 30%-100%; In the uniformly mixed hydrogel precursor solution, the solid content of component A is 1wt%-30wt%, preferably 2wt%-10wt%; the solid content of component B is 1wt%-30wt%, preferably 2wt%-10wt%; the solid content of component C is 0.1wt%-0.9wt%, preferably 0.1wt%-0.3wt%; the total solid content of component A and component B is 2wt%-60wt%, preferably 5wt%-20wt%.
9. The method for preparing a photo-crosslinked gelatin hydrogel material according to claim 6, characterized in that: The wavelength of the light source is 250-500 nm, preferably 300-450 nm, and more preferably 365 nm, 375 nm, 385 nm, 395 nm, or 405 nm.
10. The use of the photo-crosslinked gelatin hydrogel material according to any one of claims 1 to 5, characterized in that: Select one of the following applications: (1) Application of the photo-crosslinked gelatin hydrogel material as a biological ink for extrusion printing; (2) Application of the photo-crosslinked gelatin hydrogel material as bio-ink for DLP printing; (3) Application of the photo-crosslinked gelatin hydrogel material as bio-ink for volumetric printing; (4) Application of the photo-crosslinked gelatin hydrogel material in preparing microspheres by microfluidics; (5) Application of the photo-crosslinked gelatin hydrogel material in the preparation of cell, protein or drug carriers; (6) Application of the photo-crosslinked gelatin hydrogel material in the preparation of wound repair materials or hemostatic materials.
Citation Information
Patent Citations
High-strength and high-toughness photo-crosslinking hydrogel material as well as preparation method and application thereof
CN111748088A
Preparation, raw material, product and application of photo-crosslinking hydrogel material
CN112266368A
High strength and toughness photocrosslinked hydrogel material, preparation method therefor and use thereof
WO2021243835A1